2012
DOI: 10.1080/01647954.2012.733023
|View full text |Cite
|
Sign up to set email alerts
|

Solanum americanumas a reservoir of natural enemies of the tomato red spider mite,Tetranychus evansi(Acari: Tetranychidae)

Abstract: Brazilian populations of the pathogenic fungus Neozygites floridana (Weiser & Muma) Remaudière & S. Keller (Entomophthoromycotina: Entomophthorales) and the predatory mite Phytoseiulus longipes Evans (Acari: Phytoseiidae) are potential candidates for introduction into Africa for classical biological control of the tomato red spider mite, Tetranychus evansi Baker & Pritchard (Acari: Tetranychidae). The efficiency of these natural enemies against T. evansi has been demonstrated under laboratory conditions, but l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
3
0
5
Order By: Relevance
“…Bu zararlıların daha önce domates, biber ve patlıcan gibi diğer Solanaceae bitki türlerinde de konukçu olduğunun belirlenmiş olması köpek üzümü türlerinden kültür bitkilerine bulaşması açısından risk oluşturmaktadır (Soleimannejadian et al, 2006;Can & Çobanoğlu, 2010;Ozsisli & Cobanoglu, 2011). Sonuçlarımıza benzer olarak, Ribeiroa et al (2012) (Calvitti & Tsolakis, 1992;Çobanoğlu & Kumral, 2014). T.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Bu zararlıların daha önce domates, biber ve patlıcan gibi diğer Solanaceae bitki türlerinde de konukçu olduğunun belirlenmiş olması köpek üzümü türlerinden kültür bitkilerine bulaşması açısından risk oluşturmaktadır (Soleimannejadian et al, 2006;Can & Çobanoğlu, 2010;Ozsisli & Cobanoglu, 2011). Sonuçlarımıza benzer olarak, Ribeiroa et al (2012) (Calvitti & Tsolakis, 1992;Çobanoğlu & Kumral, 2014). T.…”
Section: Discussionunclassified
“…Aynı familyadan olduğu için yukarıda belirtilen kültür bitkilerinde bulunan zararlı akar türlerinin bu yabancıotlarda bulunma olasılığı da çok yüksektir. Bu bağlamda, köpek üzümü türlerinin zararlı türlere barınak olma potansiyeli sınırlı sayıda çalışmada gösterilebilmiştir (Sadana et al, 1983;Mauricio et al, 2009;Murungi et al, 2010;Ferreira & Sousa, 2011;Ribeiroa et al, 2012). Özellikle, Ferreira & Sousa (2011), S. nigrum ve buna benzer birçok yabancı ot türünün Tetranychus evansi (Baker & Prit.)…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Low prevalences of resting spores of N. tanajoae in M. tanajoa (up to 3.8%) were detected in Brazil by Delalibera Jr. et al [10], whereas higher prevalences (34–38%) were found by Elliot et al [9]. However, resting spores of Neozygites have not been found in other studies in tropical regions [13–15]. …”
Section: Introductionmentioning
confidence: 95%
“…Fungi in this genus attack small arthropods such as mealybugs, aphids, thrips and mites (2000), whereas higher prevalences (34-38%) were found by . However resting spores of Neozygites have not been found inother studies in tropical regions (ALVAREZ et al, 1993;YANINEK et al, 1996, RIBEIRO et al, 2012.…”
Section: Introductionmentioning
confidence: 96%